An evaluation of the effectiveness of an updated pre-service midwifery curriculum integrated with emergency obstetric and newborn care in Kenya: a cluster randomised controlled trial - Duncan N. Shikuku; Catherine Mwaura; Peter Nandikove; Alphonce Uyara; Helen Allott; Lucy Waweru; Lucy Nyaga; Edna Tallam; Issak Bashir; Eunice Ndirangu; Carol Bedwell; Sarah Bar-Zeev; et al. (BMC Medical Education)
Abstract Introduction Quality midwifery education is central to improving midwifery service delivery and maternal and newborn health outcomes. In many settings, midwifery educators insufficiently prepared for their teaching role and deficient curriculum compared to international standards affect the quality of healthcare provided by the midwifery graduates. This study assessed the effectiveness of an EmONC enhanced midwifery curriculum delivered by trained and mentored midwifery educators on the quality of education and student performance in Kenya. Methods A cluster randomised controlled trial in 20 midwifery colleges (12 intervention, 8 control colleges). Educators in both arms received training in teaching/EmONC skills to deliver the updated national midwifery curriculum. The intervention arm received additional 3-monthly post-training mentoring for 12 months. Educators’ knowledge and confidence in EmONC/teaching skills was assessed before and after training and at 3, 6, 9 and 12 months. Teaching skills observations at baseline and endline in both study arms were also assessed. Knowledge, self-rated confidence and three OSCE in EmONC practical skills among final year midwifery students were assessed. Linear mixed effects models were used to evaluate the effect of intervention on educators and students. Results Seventy four educators and 146 students participated. Training significantly improved educators’ mean knowledge (61.3%-73.3%) and confidence to teach EmONC (3.1–4.2 out of 5). Observed teaching skills mean scores of educators in the intervention arm were significantly higher compared to those of controls at endline (89.4%-vs-72.2%, mean difference 17.2 [95%CI, 3.2–29.8]). Mean scores for students in the intervention arm were significantly higher than those in controls for knowledge (59.6%-vs-51.3%, mean difference 8.3 [95%CI, 1.6–15.0]) and the three skills assessed (means; mean difference (95%CI): shoulder dystocia (64.5%-vs-42.7%; 21.8 (10.8–33.9); newborn resuscitation (43.9% vs 26.1%; 17.8 (2.0–33.9); and maternal shock resuscitation (56.5%-vs-39.2%; 17.3 (8.0–26.0) and combined average skills scores (55.0%-vs-36.0; 19.0 (8.7–29.5). Conclusion Training and supportive mentoring improved the quality of educators’ teaching pedagogy and EmONC skills and enhanced students’ learning. Overall performance in EmONC knowledge and skills was significantly higher for students who were taught by trained and mentored educators compared to those who received training alone. Thus, a local mentoring system is effective to enhance learning and effectiveness of an EmONC-updated midwifery curriculum.